CYTOTOXIC AND THROMBOLYTIC ACTIVITY OF ROOT EXTRACT OF MUSA PARADISIACA (FAMILY: MUSACEAE) - Manzur, Tanzila; Juhara, Fatematuj; Zaman, Sayera; Salauddin, Md; Huq, Irfanul; Arif ullah, H.M. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate for cytotoxicity and thrombolytic activity. Methods: The cytotoxic activity was investigated by using brine shrimp nauplii. The ethanol extract was prepared by dissolving them in DMSO (not more than 50 µL in 5 mL solution) with sea water (3.8% NaCl in water) using concentrations 6.25, 12.5, 25, 50, 100, 300 and 500 µg/mL. The extract was also evaluated for thrombolytic effect using clot lysis analysis at the concentration of 500µg, 800µg and 1000µg. Results:The ethanol extract of M. paradisiaca showed cytotoxic activity against brine shrimp nauplii and LC50 value was 25 µg/ mL and thrombolytic activity was also investigated in our research that the % of clot lysis were 3.27, 7.59 and 13.04 at the concentration of 500µg, 800µg and 1000µg respectively. Conclusion:This is only a preliminary study.Further studies are necessary to evaluate the exact mechanism behind these activity. Key Words: Musa paradisiaca;ethanol extract; brine shrimp nauplii:cytotoxic Activity; thrombolytic Activity